Addition of ceftaroline fosamil or vancomycin to PMMA: An in vitro comparison of biomechanical properties and anti-MRSA efficacy. (28th May 2019) - Haseeb, Amber; Ajit Singh, Vivek; Teh, Cindy Shuan Ju; Loke, Mun Fai
Background: Ceftaroline is a cephalosporin that is effective against methicillin-resistant Staphylococcus aureus (MRSA) infections. The objective of this study was to determine the feasibility of using ceftaroline-loaded Polymethyl methacrylate (PMMA) as antibiotic cement against MRSA versus vancomycin-loaded PMMA in an in vitro setting. Methods: PMMA pellets were prepared with three separate concentrations of each of the two antibiotics tested. They were tested to determine the effect of increasing concentration of antibiotics on the biomechanical properties of PMMA and antibiotic activity by measuring the zone of inhibition and broth elution assay. Results: Ceftaroline PMMA at 3 wt%, three-point bending was 37.17 ± 0.51 N ( p < 0.001) and axial loading was 41.95 N ± 0.51 ( p < 0.001). At 5-wt% vancomycin-PMMA, three-point bending was 41.65 ± 0.79 N ( p = 0.02) and axial loading was 49.49 ± 2.21 N ( p = 0.01). Stiffness of ceftroline-loaded PMMA in low and medium concentration was significantly higher than the vancomycin. The zone of inhibition for ceftaroline was higher than vancomycin. Ceftaroline at 3 wt% eluted up to 6 weeks (0.3 ± 0.1 μg/ml) above the minimum inhibitory concentration (MIC) and vancomycin at 2.5 wt% eluted up to 3 weeks, same as MIC, that is, 0.5 ± 0.0 μg/ml. Conclusions: Ceftaroline, loaded at similar concentrations as vancomycin into PMMA, is a more potent alternative based on its more favourable bioactivity and elution properties, while having a lesser effect on the mechanical properties of the cement. The use of 3-wt% ceftaroline as antibiotic laden PMMA against MRSA is recommended. It should be noted that this was an in vitro study and to determine the clinical efficacy would need prospective, controlled and randomized studies.